Proses Keputusan Adopsi Inovasi Padi Rojolele Srinuk oleh Petani (Studi Kasus di Desa Segaran, Kecamatan Delanggu, Kabupaten Klaten) - Luviansyah, Daffa; Suminah, Suminah; Permatasari, Putri (Universitas Muhammadiyah Semarang, 2023)
Segaran Village is one of the villages targeted for the development of Rojolele Srinuk rice in Klaten Regency. Farmers have an important role in efforts to develop Rojolele Srinuk rice. There is a process for reaching decisions made by farmers in adopting and the role of communication channels used at each stage of the innovation adoption decision process. The purpose of this study was to determine the development of Rojolele Srinuk rice cultivation in Segaran Village, identify the communication channels, and analyze the decision process for adopting Rojolele Srinuk rice innovation by farmers in Segaran Village. The research method in this research is a descriptive qualitative method. Data collection by in-depth interviews, observation, and document study. The results showed that the development of Rojolele Srinuk rice cultivation in Segaran Village is currently quite good. The communication channels used in the process of adopting the Rojolele Srinuk rice innovation by farmers in Segaran Village are interpersonal local and cosmopolit channels. There are farmers who continue adoption, discontinuance, later adoption, and continue rejection.